PARTY POLITICS AND DEMOCRACY - Thipprajong, Mali; Arkamathiro, Phrasamu arkom; Wijitwatchararak, Kanjira (Journal of MCU Phetchaburi Review, 2021)
Political parties are essential in the democratic regime. A political party is a political institution formed by a group or a group of persons or associations with shared opinions and common interests who wish to unite to seek power. In governing a country, It is structured as an organization with a well-organized system of control with a party executive committee and party members to operate according to the constitutionally accepted mechanism to regulate public affairs, which the government manages to benefit. Sharing of people Political refinement is an essential means of transmitting, developing or preserving political society’s political culture. In addition, in any political organization, it can be considered that political development is a desirable trait. It must be a society with a democratic regime only, so it is this political refinement to act in the structure of the political system to support the learning of members of the political community to have a culture and way of living in the regime. Substantial democracy presented by representatives of each political tune Considering the policy of an individual or group of people what to do, the person who proposes a candidate and proposes an approach is a political party. Therefore, a political party plays the role of an intermediary between the state and the people and contributes to the political will of the people. To convey and change to create the political will of the state. Through elections, therefore, political parties are necessary for democratic government.